A new species of Eupithecia Curtis (Lepidoptera: Geometridae, Larentiinae) from Turkey - Seven, Erdem; Mironov, Vladimir; Akin, Kesran (Zootaxa, 2019)
A new Eupithecia Curtis (Lepidoptera, Geometridae) species in the fletcherata group; Eupithecia nemrutica sp. n. is described from Turkey. Male and female adults, genitalia and habitats of the species are illustrated. The species is compared with Eupithecia jizlensis muelleri Hausmann, 1991.